The clinical presentation of women with symptomatic uterine fibroids requiring surgery - Maro, Eusebious (Department of Obstetrics and Gynaecology, 2025)
Uterine fibroids are the most common tumors among women of reproductive age, affecting more than 70% of women worldwide. Ethnicity influences the development of uterine fibroids and women of African origin are particularly affected. However, despite the high incidence and prevalence of uterine fibroids in African women, there is a lack of information in SSA with regard to the clinical presentation of women with uterine fibroids and their symptoms and the specific medical and/or surgical management options offered to them. This underscores the need to understand the clinical presentation of women with symptomatic uterine fibroids and describe the specific treatment offered. Methods: We reviewed in a descriptive study the clinical information of 560 women who were previously enrolled in our Fibroid Gene Study which was designed to investigate the genetic basis of uterine fibroids. Of these, 30 participants were not included in this review of their clinical presentations. Six clerking sheets had been misplaced, and 24 patients had no fibroids on histological examination. The study prospectively collected clinical information and tissue samples from women with symptomatic uterine fibroids prior to myomectomy or hysterectomy. Statistical analysis was performed using R statistical software (R Core Team 2022). Numerical variables were summarized using measure of central tendency while frequencies and proportion were used to summarize the categorical variables. Results: The mean (SD) age of 530 women who presented to Groote Schuur Hospital for surgery due to symptomatic uterine fibroids was 44.31(7.23). Of the study participants 450(84.9%) underwent a hysterectomy, 77(14.5%) had a myomectomy while information for three (0.5%) women was missing with regard to what type of surgery was performed. Mixed ancestry was the most represented ethnicity among women who had a hysterectomy and was recorded in 315(70.1%). In contrast 41(53.2%) of the women who had a myomectomy were of black ethnicity. Most of the study participants presented at the time of surgery with heavy menstrual bleeding as their main clinical complaint (n=382 (72.1%)), followed by pelvic pain (n=209 (39.4%)), dysmenorrhea (n=169 (35.2%)), pelvic mass (n=56 (10.6%)) and infertility (n=35 (6.6%)). About 15.5% of our study population who were asked, reported positive family history of uterine fibroids. Intramural uterine fibroids were reported/documented on ultrasound in 21% of the study participants. For the majority of the study participants (62%), there was no documentation in the ultrasound reports of the position of the uterine fibroids. Conclusion: Women who present with symptomatic uterine fibroids requiring surgery are of older age and present with heavy menstrual bleeding. These women will often have a sister or mother with uterine fibroids. Hysterectomy was the most common surgical option chosen for the women in our study.